AB0110 Anti-Rankl Treatment Inhibits Erosive Joint Destruction But Has No Effect on Bone Formation in the DTH Arthritis Model. (9th June 2015) - Atkinson, S.M.; Bleil, J.; Kühl, A.; Thorn, M.; Haase, C.; Skov, S.; Nansen, A.; Syrbe, U.
Abstract : Background: The delayed-type hypersensitivity arthritis (DTHA) model combines collagen type II antibody (anti-CII) treatment with local DTH induction in the footpad [1] which induces a strong arthritis accompanied by bone destruction and excessive peri-articular bone formation. Objectives: Here we analyzed the impact of osteoclasts on inflammation, joint damage and bone formation in the DTHA model. Methods: C57BL/6 mice were immunized with methylated BSA (mBSA) in CFA, given 1000 μg anti-CII four days later [1] and challenged seven days after immunization with 200 μg mBSA in PBS in one hind foot pad and with 20 μl PBS only in the other foot pad (control). Osteoclast activity was determined in vivo by fluorescence imaging using the Cat K 680 FAST probe. Receptor-activator of nuclear factor kappa B (RANKL), TRAP and Cathespin K (CatK) mRNA expression was analyzed in arthritic paw tissue by mRNA deep sequencing. TRAP5b, CTX-I and CTX-II serum levels were determined by ELISA. In situ expression of tartrate-resistant acid phosphatase (TRAP), collagen 10 (COL10) and osteocalcin was detected by immunohistochemical staining. Inflammation, erosive joint damage and peri-articular bone formation were semi-quantitatively scored. Results: In vivo imaging of osteoclast activity showed increased CatK activity on days 3 and 8 after arthritis induction in the arthritic paw. RANKL mRNA expression peaked on d3 while TRAP and CatK mRNA expression peaked on d8. Erosive joint damage was driven from the subchrondal bone marrow side. Here, TRAP-positive osteoclasts were located at the borders of a granulation tissue which eroded the subchondral bone plate. Peri-articular bone formation involved COL10 expressing hypertrophic chondrocytes as well as osteocalcin–expressing osteoblasts. Treatment with anti-RANKL antibody did not affect footpad swelling (p>0.05) but reduced the serum levels of TRAP5b (p<0.001) and CTX-I (p<0.001) and prevented the destruction of the subchondral bone plate (p<0.001) and development of the invasive granulation tissue (p<0.001) at subchondral sites. Scores of intra- and peri-articular inflammation and scores of peri-articular bone formation did not change (p>0.05). Conclusions: Inhibition of osteoclast differentiation prevents joint destruction in the DTHA model driven by the subchondral granulation tissue while leaving intra-articular and peri-articular inflammation and bone formation unaffected. Osteoclast activity might be targeted to prevent erosive damage driven from subchondral sites as for instance in sacroiliacal joints of patients with spondyloarthritis. Disclosure of Interest: None declared